Factor affecting employees’ performance / Nur Rasyidah Fudin - Fudin, Nur Rasyidah (Faculty of Business and Management, 2019)
The increased competition between the firms, and their need to respond effectively to rapidly give impact to the changing operational conditions and thus it leads to the organization to push their employees to increase their performance in order to meet that requirement. The research objective is to examine whether there is a significant relationship between employee participation, employee relation, and job involvement with employees’ performance. The target respondents in this study are employees who work in Syarikat Air Melaka Berhad (SAMB), Melaka and only 120 questionnaires were answered. The collected data will be analyze by using statistical package for social science (SPSS) software. Descriptive analysis, Reliability test, Pearson Correlation analysis and Multiple Regression will be used to analyze the collected data. The study revealed that there have significant relationship between employee participation, employee relation, and job involvement with employees’ performance. Thus, the result of this study can be helpful for the organization in order to have deeper understanding that employee participation, employee relation and job involvement give a relationship with employees’ performance.